Reconstruction of Multicultural-Based Arabic Language Curriculum: A Study of Philosophical Analysis and Its Implementation in Indonesia - Namiyah Fitriani; Fatma Dewi Adjiji; Dian Afrilianti; Rima Ayu Handayani (CV. Kayaswara, 2025)
This study aims to evaluate the weaknesses of the curriculum and design a multicultural curriculum model that can be applied in public secondary schools. Based on multicultural curriculum theory and educational philosophy from perenialism to reconstructivism, as well as the principles of the Independent Curriculum, the research uses an interpretive paradigm and a qualitative approach through literature studies. Secondary data were analyzed qualitatively descriptively. The results of the study resulted in a multicultural curriculum model that integrates all Arabic language skills (listening, speaking, reading, writing) with flexibility and contextual relevance, and accommodates cultural diversity without neglecting the core values of Arabic language learning. The contribution of this research enriches the theory of Arabic curriculum with the integration of multicultural approaches and philosophical analysis. His findings provide practical recommendations for curriculum developers and teachers to create learning that is inclusive, relevant, and serves as a tool for linguistic mastery as well as a medium for promoting intercultural understanding and diversity values.